State and trait anxiety among medical staff during the first month of COVID-19 pandemic: A sample from Turkey - (:unkn) unknown (SAGE PUBLICATIONS INC, 2021)
Objectives During the COVID-19 pandemic, excessive workload, a rapidly changing workplace environment, the danger of carrying the virus and transmitting the disease to their families, relatives and those they live with creates stress for the medical workers. In our study, we aimed to evaluate the state and trait anxiety levels of healthcare professionals who encounter patients with suspected COVID-19 infection and related factors. Method Data were collected from healthcare professionals working with patients diagnosed or suspected with COVID-19 via online self-report questionnaire between 9-19 April 2020. The state (STAI-S) and trait anxiety (STAI-T) scale was used to measure anxiety. Results A total of 291 healthcare professionals, 216 women and 75 men, participated in the study. Women's state and trait anxiety were significantly higher than men's. 11 participants without any lifetime psychiatric illness experienced psychiatric symptoms and consulted to a psychiatrist. The state anxiety of those who have children, nurses and those working in branches directly related to the pandemic (Infectious Diseases, Respiratory Diseases, Emergency Medicine, Internal Medicine, Radiology, Anesthesiology and Reanimation) was higher than others. The state anxiety of those who thought they were not protected with personal protective equipment and those who did not stay in their own home was higher than others. Conclusions At the forefront of the fight against COVID-19, there are medical personnel who pay a serious psychological cost. Especially in terms of anxiety, we should pay attention to women, workers with children, nurses and people working in branches that are directly related to pandemics.
Keywords: coronavirus; medical staff; professional experience; behavioral response; isolation measures; PSYCHOLOGICAL IMPACT; MENTAL-HEALTH; CARE; WORKERS